Too Much or Too Little Messaging? Situational Determinants of Guilt About Mobile Messaging. Issue 2 (20th February 2021) - Halfmann, Annabell; Meier, Adrian; Reinecke, Leonard
Abstract: Mobile messaging has been associated with guilt. Guilt about too much messaging may result from self-control failures during goal conflicts. Conversely, guilt about too little messaging may result from violating the salient norm to be available. This research considers both boundary conditions of guilt about mobile communication—goal conflicts and availability norm salience—simultaneously for the first time. We conducted two preregistered experiments to investigate their interplay. Results from a vignette experiment, but not from a laboratory experiment, support the hypotheses that goal conflicts trigger guilt about using messengers and that guilt about not using messengers arises if the availability norm is salient. In both studies, using messengers elicited more guilt than not using messengers. The boundary conditions did not interact in influencing guilt. Overall, this research emphasizes the importance of self-control, norms, and usage contexts when studying effects of mobile media use on emotional well-being. Lay Summary: In this article, we examine feelings of guilt about the use of mobile messaging. On the one hand, we assume that guilt can arise if we message too much when we should be doing something else. On the other hand, we may feel guilty about too little messaging, i.e., when others expect us to be readily available via messaging, but we do not meet that expectation. These two assumptions were supported as seen in the results of an experiment where the participants were asked to imagine messaging (or not using messaging) in certain situations. However, in a second experiment where the participants actually experienced situations that we assumed would cause guilt, the expected feelings of guilt did not occur. In both studies, using messaging when the individual should have been doing something else caused stronger feelings of guilt than not being available for messaging. Previous research suggests that the resulting feelings of guilt can reduce our well-being. We therefore discuss our findings in terms of how users can avoid the negative effects of messenger use on their well-being.